2020
DOI: 10.1155/2020/1713904
|View full text |Cite
|
Sign up to set email alerts
|

Assistant Diagnosis of Basal Cell Carcinoma and Seborrheic Keratosis in Chinese Population Using Convolutional Neural Network

Abstract: Objectives. To evaluate CNN models’ performance of identifying the clinical images of basal cell carcinoma (BCC) and seborrheic keratosis (SK) and to compare their performance with that of dermatologists. Methods. We constructed a Chinese skin diseases dataset which includes 1456 BCC and 1843 SK clinical images and the corresponding medical history. We evaluated the performance using four mainstream CNN structures and transfer learning techniques. We explored the interpretability of the CNN model and compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…A previous study reported an artificial intelligence-assisted decision making system for skin tumors with a recognition rate of 91.2% for [17]. Additionally, in rosacea, psoriasis, eczema, and atopic dermatitis, deep learning has been proven to have excellent diagnostic or classification capabilities [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported an artificial intelligence-assisted decision making system for skin tumors with a recognition rate of 91.2% for [17]. Additionally, in rosacea, psoriasis, eczema, and atopic dermatitis, deep learning has been proven to have excellent diagnostic or classification capabilities [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…used a convolutional neural network to grade the severity of facial images of patients with acne, and obtained the best classification accuracy of 67% [ 17 ]. Additionally, in rosacea, psoriasis, eczema, and atopic dermatitis, deep learning has been proven to have excellent diagnostic or classification capabilities [ 18 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the field of skin oncology, we have studied less. According to other studies, there has been the first dataset of skin tumors of BCC and SK races in China [ 28 ]. In the following research, we will continue to make progress and update our analytical conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…All 22 studies were performed between 2002 and 2021 [23][24][25][26][27][28][29][30][31][32], with 11 (50%) studies published between 2020 and 2021 [33][34][35][36][37][38][39][40][41][42][43][44]. An overview of study characteristics is displayed in Table 2.…”
Section: Methodsmentioning
confidence: 99%